Stable tunable single-longitudinal-mode semiconductor optical amplifier erbium-doped fiber ring lasers for 10 Gbps transmission over 50 km single-mode fiber - Tseng, Chih-Lung; Liu, Cheng-Kuang; Lin, Zih-Rong; Chiu, Chia-Ming; Lai, Kuo-Chien (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We demonstrate a stable and tunable single-longitudinal-mode SOA-EDF ring laser for high-speed data transmission systems. The laser is constructed by incorporating an SOA into the EDF ring cavity. The SOA acts as a saturable absorption high-pass filter to suppress cavity mode partition noise at low frequencies. Such design ensures a stable and single-frequency operation for more than several hours. The ring laser has a 30 nm tuning range in the C band and a 0.8 nm wavelength spacing to match 100-GHz ITU-T grids. The variation in the maximum power is smaller than 0.02 dB and the optical signal-to-noise ratio is above 53 dB. By employing this fiber laser, a 10 Gbps non-return zero data transmission over a 50 km long single-mode fiber with a power penalty less than 2.4 dB is demonstrated.
Optica Applicata, Vol. 40, 2010, nr 4, s. 927-933
Keywords: optyka; optical fiber transmission; tunable fiber ring lasers; erbium-doped fiber; semiconductor optical amplifier; single-longitudinal-mode; saturable absorber